Portal satisfaction: a strategy for customer retention in the electronic era / Chuah Kee Yong, T. Ramayah and Nabsiah Abdul Wahid (Faculty of Business and Management ; UiTM Press, 2006)
The effects of e-Commerce on globalization of economic activities have created opportunity as well as threat to the growth of Small and Medium Enterprises (SMEs). There is a need to develop a better understanding of how subscribers of trade portal evaluate e-services, satisfaction and develop e-loyalty. This research investigated the relationship between core service, supporting services, user interface, perceived value and subscriber satisfaction and loyalty. Data was collected by means of a questionnaire survey distributed to SMEs in Malaysia. The results revealed that user interface and perceived value were the most important drivers of subscriber satisfaction with supporting services a significant but less important driver. A direct link between subscriber satisfaction and loyalty was established. No significant direct effects were found of satisfaction with core service. A positive effect of satisfaction on loyalty of subscriber to continue using the portal was found. A major conclusion was that both perceived value and e-services dimensions should be incorporated into subscriber satisfaction models to provide a more complete picture of the drivers of satisfaction.